"You Write, He'll Fight" : an Analysis of World War II Letters From American Women 1941-1945 - Rohan, Rebecca S. (My University, 2011)
In the age before instant electronic communication, letter writing played a key role in maintaining personal relationships. During World War II, women on the home front expressed their delight and frustration with wartime life through their correspondence to soldiers overseas. In the 1940s all available resources were utilized in the war effort, including the potential of home front letters to raise the morale of soldiers overseas. Additionally, the necessity of timely mail delivery combined with the limited availability of valuable cargo space resulted in the new government-developed Victory Mail program. A media campaign that advised women on appropriate topics also promoted frequent letter writing. By juxtaposing two types of primary source documents, women's letters and the writing guidelines they were supposed to follow, this thesis analyzes the degree to which women adhered to the letter writing recommendations.
Keywords: Letter writing--United States--History--20th century; World War, 1939-1945--Communications; Women--United States--Correspondence; V-mail--United States